Pneumocystis pneumonia in HIV-positive and non-HIV patients: a retrospective comparative study from a lower-middle income country - Maaha Ayub; Mustafa Bin Ali Zubairi; Najia Ghanchi; Safia Awan; Kauser Jabeen; Ali Zubairi (Monaldi Archives for Chest Disease, 2024)
In this study, we compared the predisposing factors, key demographic and clinical characteristics, clinical outcomes, and factors associated with poor prognosis in pneumocystis pneumonia (PCP) infection among the human immunodeficiency virus (HIV)-positive and non-HIV patient populations. This retrospective analysis was conducted at the Aga Khan University Hospital, Karachi, via the collection and analysis of patient records with a diagnosis of "pneumocystosis" between January 2015 and October 2020. Additionally, the laboratory database was evaluated, and patients with a laboratory-confirmed diagnosis of PCP were included. During the study period, 52 laboratory-confirmed hospitalized PCP patients were identified. Of these, 23 and 29 patients were diagnosed using microscopy and polymerase chain reaction, respectively. 34.6% of our patients were HIV positive, with a median CD4 count of 20.5 cells/mm3 (range: 10.7-50.5). Other conditions identified were corticosteroid use, autoimmune diseases, malignancy, radiation, and chemotherapy. On chest imaging, consolidation was found in 30%, ground-glass opacities in 24%, and nodular infiltrates in 20% of the cases. HIV-positive patients had a lower hemoglobin level and a higher level of β-D-glucan at the time of admission, whereas non-HIV patients were found to have more co-morbid conditions than HIV patients. We observed no difference in clinical outcomes between the two populations. Factors associated with a poor prognosis among our patients included concomitant infections at the time of diagnosis, the need for invasive mechanical ventilation, and a longer duration of stay in the hospital as well as the intensive care unit.